Comparative study of lymph node dissection, and oncological outcomes of laparoscopic and open radical nephroureterectomy for patients with urothelial carcinoma of the upper urinary tract undergoing regional lymph node dissection. (29th September 2018) - Abe, Takashige; Kondo, Tsunenori; Harabayashi, Toru; Takada, Norikata; Matsumoto, Ryuji; Osawa, Takahiro; Minami, Keita; Nagamori, Satoshi; Maruyama, Satoru; Murai, Sachiyo; Tanabe, Kazunari; Shinohara, Nobuo
Abstract : We revealed the feasibility of lymph node dissection (LND) with a laparoscopic approach and the equivalent oncological outcome of laparoscopic nephroureterectomy compared with open nephroureterectomy when regional LND is performed. Abstract: Objective: To assess the number of lymph nodes removed as a surrogate marker of the extent of lymph node dissection, and compare survival outcomes between laparoscopic radical nephroureterectomy (LRNU) and open radical nephroureterectomy (ORNU) in patients undergoing standardized lymph node dissection. Methods: We retrospectively analyzed the data of 214 cTanyN0M0 patients undergoing radical NU with regional lymph node dissection according to the tumor location. The Kaplan–Meier method and Cox hazards model were utilized for survival analyses, including recurrence-free survival (RFS), cancer-specific survival (CSS) and overall survival (OS). Results: A total of 114 patients underwent LRNU and 100 underwent ORNU. There was no significant difference in the pT stage, pN stage, or tumor grade, but distal ureteral tumors were more frequent in the LRNU group. The number of lymph nodes removed did not differ between the two groups [LRNU: 12 (median), ORNU: 11.5, P = 0.3852]. Lymph node metastasis was pathologically identified in 19 patients (8.9%). The 5-year RFS (ORNU: 71.7%, LRNU: 74%, P = 0.7829), CSS (77.8 and, 80%, P = 0.8441) and OS (72.8, and 75.9%, P = 0.3456) did not differ between the two groups. In the sub-analysis of pT3/4 patients ( n = 83), there were no significant differences in RFS, CSS, or OS between the two groups, although Kaplan–Meier survival curves were slightly better for those receiving ORNU. In the multivariate model, LRNU was not significantly correlated with a poorer RFS, CSS or OS. Conclusion: Our data support the feasibility of lymph node dissection with a laparoscopic approach and the equivalent oncological outcome of LRNU compared with ORNU when regional lymph node dissection is performed. However, LRNU should be performed after careful patient selection for advanced disease.